Liquid-liquid equilibria of the phosphoric acid, ester and water ternary system (Rudarsko-geološko-naftni zbornik, 2020)
This paper presents an experimental methodology used for the determination of liquid-liquid equilibrium (LLE) data of the ternary system (phosphoric acid, ester and water). This experimental methodology represents the determination of phosphoric acid linked with different aquatic systems. In this study, an ester was selected as an organic solvent for the recovery of phosphoric acid from waste water. The binodal curve and the tie lines have been prominent. The ternary system (water + phosphoric acid + ester) was studied at three temperatures i.e. 25, 35 and 45 °C (298, 313 and 323 K). The results indicate that the extraction of phosphoric acid by a solvent is possible in aquatic systems. The results are dis- cussed.